2019
DOI: 10.1111/1471-0307.12638
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity of Livanjski cheese with the emphasis on lactic acid bacteria based on culture‐dependent and sequencing method

Abstract: The microbial diversity of artisanal Livanjski cheese from traditional farms and dairies was analysed. The polyphasic approach included the isolation of microorganisms by using culture-dependent methods and the identification of viable isolates by sequencing methods. In total, 159 isolates were identified, including five strains of yeast and 15 strains of fungi. Twenty-two species of homofermentative and heterofermentative lactic acid bacteria were classified. The Shannon-Wiener index of diversity ranged from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
(58 reference statements)
1
9
1
Order By: Relevance
“…While some studies show that cheese yield is higher in cows than goat (Rasheed et al, 2016), our study and others show the opposite (Hamidi et al, 2018;Mallatou & Pappa, 2005). Different factors might produce this interspecific difference, including those related to the milk composition and quality such as genetic variants of casein, fat and protein (Banks et al, 1981;Fenelon & Guinee, 1999;Verdier-Metz et al, 2001), seasonal variations (Sánchez-Gamboa et al, 2018), microbial counts and diversity (Vladimír et al, 2020) and cheese-processing methodology (Lawrence, 1993). In our study, "Bouhezza"-processing methodology and season are the same, however, we found higher fat and protein content in goat compared to cow milk, which probably contributed to the increase in cheese yield (Lucey & Kelly, 1994).…”
Section: Cheese Yields Analysiscontrasting
confidence: 45%
“…While some studies show that cheese yield is higher in cows than goat (Rasheed et al, 2016), our study and others show the opposite (Hamidi et al, 2018;Mallatou & Pappa, 2005). Different factors might produce this interspecific difference, including those related to the milk composition and quality such as genetic variants of casein, fat and protein (Banks et al, 1981;Fenelon & Guinee, 1999;Verdier-Metz et al, 2001), seasonal variations (Sánchez-Gamboa et al, 2018), microbial counts and diversity (Vladimír et al, 2020) and cheese-processing methodology (Lawrence, 1993). In our study, "Bouhezza"-processing methodology and season are the same, however, we found higher fat and protein content in goat compared to cow milk, which probably contributed to the increase in cheese yield (Lucey & Kelly, 1994).…”
Section: Cheese Yields Analysiscontrasting
confidence: 45%
“…pH results are in agreement with those recorded for "Anevato" cheese produced in Greece (pH value 4.64-4.47) (Hatzikamari et al, 1999) and "Picodon" goat cheese produced in France (pH value 4.5) (Leclercq-Perlat et al, 2019) ; or ripened at the early stages of ripening, like in traditional Spanish cheese Babia-Laciana (pH value 4.44) (Franco et al, 2003). However, pH results are slightly lower compared to those recorded for Mexican cheese produced from raw milk "Chihuahua" (pH value 5.2) (Sánchez-Gamboa et al, 2018) ;"Livanjski" cheese produced from raw ewe and/or cow milk in Bosnia and Hercegovina (pH value 5.45) (Vladimír et al, 2020) ; or Brazilian cheese produced from raw or pasteurized milk "Coalho" (pH value 5.2) (Queiroga et al, 2013), and other raw goat's milk cheeses, either fresh like "Vlasina" produced in Serbia (pH value 5.1-5.2) (Terzic-Vidojevic et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
“…Protocol for the production of "Jben" cheese. flora of milk (Cantor et al, 2004), or seasonal variations (Sánchez-Gamboa et al, 2018), microbial counts and diversity (Vladimír et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lb. helveticus strains and other facultative heterofermentative lactobacilli have been shown to play a significant role in the improvement of the texture and flavor of hard cheese during ripening (Visser, 1993; Vladimír, Miloslava, Markéta, Jaroslava, & Petr, 2020). Lactobacillus helveticus was demonstrated to have better performance (i.e., in terms of stretchability and melting) than Lb.…”
Section: Applications Of Ceps In Food Technology and Human Healthmentioning
confidence: 99%